PENGARUH REVIEW PRODUK, RATING DAN KEPERCAYAAN MASYARAKAT TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOOPE (STUDI KASUS DI DESA GONILAN KARTASURA) - Ananda Puput Ayuningrum; Muzakar Isa (Universitas Muhammadiyah Surakarta, 2024)
Analyzing the influence of product reviews, ratings and public trust on purchasing decisions on the Shopee e-commerce platform. The success of a product on the market is not only determined by the quality of the product itself, but also by consumer interactions through reviews and ratings provided. The research method used was an online survey involving respondents who were active in Gonilan Kartasura Village shopping at Shopee. Data was collected through questionnaires distributed randomly to Shopee users. Data analysis is carried out using statistical techniques, for example regression to assess the influence of the variables studied. It is hoped that the results of this research will provide further understanding of how product reviews, ratings and public trust contribute to purchasing decisions on Shopee. With this understanding, business people and marketers can optimize their strategies in building consumer trust, improving product quality, and utilizing positive reviews and ratings to increase sales on e-commerce platforms.